Prophylactic negative pressure wound therapy is not effective for preventing driveline infection following left ventricular assist device implantation. Issue 3 (12th November 2022) - Tsuji, Masaki; Kakuda, Nobutaka; Bujo, Chie; Saito, Akihito; Ishida, Junichi; Amiya, Eisuke; Hatano, Masaru; Shimada, Asako; Imai, Hiroko; Kimura, Mitsutoshi; Ando, Masahiko; Kinoshita, Osamu; et al.
Abstract: Background: Driveline infection (DLI) following left ventricular assist device (LVAD) implantation remains an unresolved problem. Negative pressure wound therapy (NPWT) promotes wound healing by applying negative pressure on the surface of the wound. Recently, the prophylactic application of NPWT to closed surgical incisions has decreased surgical site infections in various postsurgical settings. Therefore, we evaluated the efficacy and safety of prophylactic NPWT for preventing DLI in patients with LVAD implantation. Methods: Prophylactic NPWT was provided to 50 patients who received continuous‐flow LVADs as bridge‐to‐transplant therapy at our institution between May 2018 and October 2020 (NPWT group). The negative pressure dressing was applied immediately after surgery and retained on the driveline exit site for 7 days with a continuous application of −125 mm Hg negative pressure. The primary outcome was DLI within 1 year of LVAD implantation. We compared the rate of DLI incidence in the NPWT group with that in the historical control cohort (50 patients) treated with the standard dressing (SD) who received LVAD implantation between July 2015 and April 2018 (SD group). Results: No severe complications were associated with the NPWT. During the follow‐up period, DLI was diagnosed in 16 participants (32%) in the NPWT group and 21 participants (42%) in the SD group. The rates of DLI incidence and freedom from DLI did not differ between groups ( p  = 0.30 and p  = 0.63). Conclusions: Prophylactic NPWT at the driveline exit site was safe following LVAD implantation. However, it did not significantly reduce the risk of DLI. Abstract : Prophylactic negative pressure wound therapy (NPWT) was provided to 50 patients who underwent LVAD implantation and retained on the driveline exit site for 7 days with a continuous application of −125 mm Hg negative pressure. The incidence of driveline infection (DLI) was compared between prophylactic NPWT and standard dressing (SD) group. Prophylactic NPWT at the driveline exit site was safe following LVAD implantation, however, it did not reduce the risk of DLI.